You are given the first two steps. You are to
finish simplifying by supplying three more steps.
Original expression given to
simplify: 4c + 3(2 + c) =
First step (given): Use distributive
principle to remove parentheses 4c + 6 + 3c =
Second step (given):
Put the terms which contain "c"
next to each other in front: 4c + 3c + 6 =
Third step (not given):
Use the distributive law in
reverse to put c outside a
parentheses with 4 + 3 inside c(4 + 3) + 6 =
Fourth step (not given):
Add the terms in the parentheses
4 + 3 gives 7 c(7) + 6 =
Fifth step (not given)
c(7) can be written as 7c 7c + 6
That is simplified as far as possible.
So that's the final answer.